A most interesting problem : what Darwin's Descent of man got right and wrong about human evolution - DeSilva, Jeremy, 1976- (Princeton University Press, 2021)
"In 1859, Charles Darwin proposed a mechanism for biological evolution in his most famous work, On the Origin of Species. However, Origin makes little mention of humans. Despite this, Darwin thought deeply about humans and in 1871 published The Descent of Man, his influential and controversial book in which he applied evolutionary theory to humans and detailed his theory of sexual selection. February 2021 will mark the 150th anniversay of it's publication. In A Most Interesting Problem, twelve leading anthropologists, biologists, and journalists revisit The Descent. Following the same organization as the first edition of Descent - less the large section on sexual selection -- each author reviews what Darwin wrote in Descent, comparing his words to what we now know now. There are chapters on evidence for human evolution, our place in the family tree, the origins of civilization, human races, intelligence, and sex differences. An introduction by Darwin biographer and historian Janet Browne provides context for Descent and a conclusion by Science magazine journalist Ann Gibbons looks to the future of the study of human evolution. All the chapters are written with a broad audience in mind. Ultimately, readers learn that Darwin was remarkably prophetic in some of his predictions, such as that the earliest human fossils would be discovered in Africa. But he was wrong in other areas, particularly in regards to variations between the sexes and races. Thus, A Most Interesting Problem is not so much a celebration of Darwin as it is a tribute to how science works, how scientific ideas are tested, and the role of evidence in helping structure narratives of human origins. The reader is left with a view of how far we have come in our quest for understanding human origins, biological variation, behavior, and evolution"--